UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENERAPKAN PENDEKATAN RESOURCE BASED LEARNING PADA MATERI BANGUN RUANG SISI DATAR - Yusuf, Rahman Ramadhan; Fachruddin S., M.; Yensy, Nurul Astuty (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2017)
The study aims to find out how to improve learning activities and student learning outcomes by applying Resource Based Learning approach. This research is a Classroom Action Research with data collection technique through observation sheet of learning activity and test of learning result. Subjects in the study were Class VIII 2 SMP Negeri 3 Bengkulu City academic year 2016/2017 amounted to 40 students. The results showed an increase in student learning activities conducted by learning various sources such as, LKPD, math books, internet resources and props. Increased student learning activity can be seen from the average score of observation sheet of student learning activities on the cycle I to cycle III is 23.50 (active enough); 26.67 (active enough); 30 (active). Student learning outcomes are improved by using LKPD and props. Improvement of student learning outcomes seen from the average value of students in the cycle I until the third cycle of 71.06; 81.00; 84.02 with the percentage of learning mastery that is 50%; 77.50%; 87.50%. Keywords: Resource Based Learning Approach, Learning Activities and Learning Outcomes